How Did Depositors React to Bank Risks During the Covid-19 Outbreak in Indonesia? - Tumbelaka, Indra (The International Journal of Financial Systems, 2023)
The Covid-19 outbreak provides a unique setting to examine the association between deposits and bank risk, including loan risk, as both deposits and loan risk increased significantly during the outbreak. Employing dynamic regression models in datasets from the Indonesian banking industry before and during the Covid-19 outbreak, this study provides new evidence that depositor discipline is stronger during the outbreak, as depositors are more sensitive to loan risk. The findings are different from prior studies in that depositor discipline tends to diminish during the crisis period. Furthermore, this study confirms the effectiveness of the deposit insurance system implementation, as uninsured depositors exercise stronger discipline. Last but not least, this study documents that depositor discipline is weaker in government banks as those banks are perceived as having implicit guarantees from the government.